2020
DOI: 10.3390/antiox9080703
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Antioxidant Signatures in Hyperthermophilic Archaea

Abstract: To fight reactive oxygen species (ROS) produced by both the metabolism and strongly oxidative habitats, hyperthermophilic archaea are equipped with an array of antioxidant enzymes whose role is to protect the biological macromolecules from oxidative damage. The most common ROS, such as superoxide radical (O2−.) and hydrogen peroxide (H2O2), are scavenged by superoxide dismutase, peroxiredoxins, and catalase. These enzymes, together with thioredoxin, protein disulfide oxidoreductase, and thioredoxin reductase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 114 publications
3
21
0
Order By: Relevance
“…MAR08-33, this forms a separated clade with other Euryarchaeota organisms (not acidophiles) and some Deltaproteobacteria (Figure S3). The low presence in Archaea has been reported previously, as organisms that have SOD usually do not have catalases [21] and as previously discussed we identified SOD in most acidophilic genomes with the exception of Aciduliprofundum. The result of mixed origin clades in the phylogenetic reconstruction where Archaea and Bacteria share the same clade suggests that HGT between domains could play a major role in the evolution of catalases.…”
Section: Catalasesupporting
confidence: 85%
See 2 more Smart Citations
“…MAR08-33, this forms a separated clade with other Euryarchaeota organisms (not acidophiles) and some Deltaproteobacteria (Figure S3). The low presence in Archaea has been reported previously, as organisms that have SOD usually do not have catalases [21] and as previously discussed we identified SOD in most acidophilic genomes with the exception of Aciduliprofundum. The result of mixed origin clades in the phylogenetic reconstruction where Archaea and Bacteria share the same clade suggests that HGT between domains could play a major role in the evolution of catalases.…”
Section: Catalasesupporting
confidence: 85%
“…The wide conservation across organisms of superoxide dismutase, peroxiredoxin, and rubrerythrin in both anaerobic and aerobic organisms, could suggest an ancestral origin of these proteins [82,106,107], and that they were evolved in similar environments to the early LUCA in response to local concentrations of oxygen before the GOE [108]. It has been previously reported that multiple mechanisms for oxidative stress response are found in hyperthermophiles [21] and we identified a similar pattern in acidophiles with no major differences across lifestyles (such as aerobic versus anaerobic or thermophiles versus mesophiles). Instead, the distribution of oxidative stress response mechanisms present in each organism seems to be largely determined by phylogeny.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Later on, it was reported from other haloarchaea, including Halobacterium saccharovorum , Haloarcula ( Halobacterium ) marismortui , Haloarcula californiae , Halococcus sp. LS-1), and Haloferax ( Halobacterium ) volcanii [ 77 , 78 ]. Bacterioferritin comigratory protein 1 (Bcp1) belongs to the Prx family, isolated from hyperthermophilic archaeon Sulfolobus solfataricus , which has been characterized as an antioxidant that inhibits H 2 O 2 -induced apoptosis in H9c2 rat cardiomyoblast cells [ 79 ].…”
Section: Microorganisms As a Source Of Antioxidant Compoundsmentioning
confidence: 99%
“…Rbr is a member of the ferritin-like superfamily [71] and has been implicated in stress survival in many bacteria [72] and archaea [73]. It has been experimentally verified to function as a scavenger of ROS using a di-iron center to reduce H 2 O 2 and organic hyperperoxide to water [74][75][76][77][78].…”
Section: Rubrerythrin and Neighborhood Genesmentioning
confidence: 99%